The Jewish-Christian Dialogue Jason and Papiscus in Light of the Sinaiticus Fragment - Tolley, Harry (Harvard theological review, 2021)
For centuries, the lost Jewish-Christian dialogue Jason and Papiscus was known only through various quotations and summaries from Patristic sources. This changed in 2011 with the publication of a newly discovered, large fragment of Jason and Papiscus known as the Sinaiticus fragment. The current article examines the Sinaiticus fragment, compares it to the previously known remnants of Jason and Papiscus and examines the information from the fragment in relation to other texts. Several important new observations are obtained as a result. This article-for the first time-unites the Sinaiticus fragment with all of the Patristic material related to Jason and Papiscus in one appendix, with all entries newly translated by the author with updated notes. This article also contains new digital images of the Sinaiticus fragment.